The profile of rheumatic heart disease at a tertiary hospital in KwaZulu-Natal, South Africa - Naidoo, D. P. (SA Heart Journal, 2024)
Background: Rheumatic heart disease (RHD) is a disease of poverty and a significant public health concern in developing countries. There is little data on the profile of RHD in KwaZulu-Natal (KZN), South Africa. Objectives: To describe the demographic, clinical profile, and outcomes of RHD in patients referred to a tertiary cardiology facility in KwaZulu-Natal. Methods: This is a 5-year (2012 - 2016) retrospective analysis of all patients with RHD referred to the cardiology department at Inkosi Albert Central Luthuli Hospital (IALCH). A structured format was used to extract demographic, clinical, echocardiographic and outcome data of 981 eligible patients aged >12 years. Descriptive analysis was used to report on quantitative data and logistic regression was used to identify significant associations and independent variables. Results: The majority of patients were Black (87.9%); the median age was 24 years (IQR 15 - 36 years) and the female to male ratio was 2.3:1. Dyspnoea (92.2%) was the commonest presenting symptom and mitral regurgitation (56.4%) was the commonest valve lesion. The most frequent complications at presentation were atrial fibrillation (AF) (44.9%) followed by heart failure (HF) (28.6%). AF mostly affected the 41 - 60 year age group (OR 2.075, 95% CI 1.22 - 3.52, p=0.007). Compared to the adolescent group (13 -2 0 years), HF was less common in the 21 - 40 years and 41 - 60 years age groups (OR 0.455, 95% CI 0.286 - 0.723, p=001 and OR 0.495, 95% CI 0.288 - 0.852, p=0.011, respectively). Valve replacement was performed in 723 (88.4%) – (mitral valve 62.2%; aortic valve 4.8%; mitral and aortic valves 29%; 3 valve surgeries 4%) – of the 818 patients who had interventional procedures. The mortality rate was high at 20.1%. Mortality was highest in the younger patients (<20 years of age) (p=0.016). Predictors of death were severe disease at a young age (OR 1.268, 95% CI 1.050 - 1.532, p=0.013) and double valve replacement (OR 1.521, 95% CI 1.009 - 2.229, p=0.045). Conclusion: RHD remains a significant cause of morbidity and mortality in KZN. HF during the teenage years reflects ongoing carditis with haemodynamic failure resulting in death if unoperated.